2021
DOI: 10.1111/apha.13624
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in fatal ventricular arrhythmias

Abstract: Ventricular fibrillation (VF) and sudden cardiac arrest (SCA) remain some of the most important public health concerns worldwide. For the past 50 years, the recommendation in the Advanced Cardiac Life Support (ACLS) guidelines has been that defibrillation is the only option for shockable cardiac arrest. There is growing evidence to demonstrate that mitochondria play a vital role in the outcome of postresuscitation cardiac function. Although targeting mitochondria to improve resuscitation outcome following card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Cardiac arrest, recognized as major stress, causes severe metabolic derangements and global ischemia/reperfusion (IR) injury [ 25 ]. The connections between cardiac IR injury, fatal ventricular arrhythmias, and cardiac arrest have been well established across preclinical and clinical studies [ 30 , 31 ]. These links also affect the endocrine glands, including the pancreas, and possibly lead to reduced hormonal synthesis, resulting in lower insulin and glucagon-like peptide 1 (GLP-1) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac arrest, recognized as major stress, causes severe metabolic derangements and global ischemia/reperfusion (IR) injury [ 25 ]. The connections between cardiac IR injury, fatal ventricular arrhythmias, and cardiac arrest have been well established across preclinical and clinical studies [ 30 , 31 ]. These links also affect the endocrine glands, including the pancreas, and possibly lead to reduced hormonal synthesis, resulting in lower insulin and glucagon-like peptide 1 (GLP-1) levels.…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrated that calcium administration during cardiac arrest without certain indications is associated with unfavorable outcomes, possibly because of effects of reperfusion injury to the ischemic heart, brain, and other vital organs mediated by calcium. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in mitochondrial function are a hallmark of cardiac diseases such as ventricular arrhythmias, sudden cardiac arrest, and cardiomyopathies. Wongtanasarasin summarizes data from in vitro, in vivo, and ex vivo studies on rodents regarding mitochondrial alterations in ventricular arrhythmias 4 . During an ischaemic episode, when oxygen is temporarily not available, a switch to anaerobic glycolysis occurs, and lactic acid release lowers the cytosolic pH.…”
Section: Figurementioning
confidence: 99%
“…Wongtanasarasin summarizes data from in vitro, in vivo, and ex vivo studies on rodents regarding mitochondrial alterations in ventricular arrhythmias. 4 During an ischaemic episode, when oxygen is temporarily not available, a switch to anaerobic glycolysis occurs, and lactic acid release lowers the cytosolic pH. The switch from aerobic to anaerobic glycolysis is named the Warburg effect and is frequently found in cancer cells, too, although oxygen is available.…”
mentioning
confidence: 99%